The role of external debt in economic growth of Indonesia - A blessing or burden? - Azam, Muhammad; Emirullah, Chandra; Prabhakar, Akhilesh Chandra; Khan, A. Qayyum (IDOSI Publications, 2013)
Today external debt situation is one of great concerns particularly for developing countries. The ongoing debt crisis in several European countries has the potential of creating external shocks to these countries but at the same time it shows the importance of managing well their debt. Several developing countries including Indonesia have faced stern economic problems in the past due to a high level of external debt.On the other hand, economic growth is vital to improve social welfare.This study analyzes the impact of external debt on economic growthof Indonesia.The method of least squares is used for parameters estimation. The main finding of the study shows external debthasa negativeimpact on economic growth during the period under the study.Thus, external debtis not a blessing but rather a burden for Indonesia. The finding suggests the importance of controlling external debt both, public and private, as well as enhancingdebt management effectiveness.